Beyond benefits: Towards a recreational ecosystem services interpretive framework. (2nd October 2020) - Rice, William L.; Newman, Peter; Taff, B. Derrick; Zipp, Katherine Y.; Miller, Zachary D.
ABSTRACT: The challenge of managing protected areas to purvey benefits through visitor experiences has been a major subject of research within the fields of recreation and leisure. Driver and others have advocated for the benefits approach to leisure with relative success. However, this largely-social approach discounts the role of the setting in purveying benefits and the tradeoffs managers must make between ecological and visitor wellbeing. In an emerging body of literature, use-values inherent to recreation are often referred to as recreational ecosystem services. In this approach, recreational outcomes are analysed in the context of the ecological processes through which they are provisioned. It is theorised that a union between the management concepts of recreational ecosystem services and the benefits approach to leisure has the potential to improve the management of protected areas. This manuscript introduces the Recreational Ecosystem Services Interpretive Framework through a review of the existing theory and literature on both approaches to protected area management.